Polyethylene Terephthalate/Acryl Butadiene Styrene Copolymer Incorporated with Oak Shell, Potassium Sorbate and Egg Shell Nanoparticles for Food Packaging Applications: Control of Bacteria Growth, Physical and Mechanical Properties. Issue 4 (November 2017) - Mousavi, Seyyed Mojtaba; Hashemi, Seyyed Alireza; Amani, Ali Mohammad; Saed, Hesam; Jahandideh, Sara; Mojoudi, Fatemeh
In this study, the effect of renewable and degradable resources including Oak shell, potassium sorbate and egg shell nanoparticles on the overall properties of polyethylene terephthalate (PET)/acryl butadiene styrene (ABS) were investigated. In this regard, the effect of mentioned additives on the mechanical properties, oxygen permeability, water absorption rate and anti-microbial properties of recycled PET/ABS blend were examined. The results revealed that the addition of ABS to PET can lead to an increase in tensile strength, while it can lead to a decrease in the elongation at break and Young's modulus. Moreover, the addition of Oak shell and potassium sorbate to the PET/ABS mixture can enhance the antimicrobial properties. However, these additives can lead to a significant increase in the water absorption and oxygen permeability within the PET/ABS mixture. On the other hand, reinforcement of PET/ABS with egg shell nanoparticles not only improves the mechanical properties of PET/ABS but also can lead to a decrease in the water absorption and oxygen permeability compared with neat PET/ABS. The main aim of this study is to develop anti-bacterial and degradable plastic structures based on recycled PET/ABS to find a solution for recycling plastic based scraps or improving their natural degradability.